Apakah Kualitas Audit Dapat Mempengaruhi Agresivitas Pajak ? - Muhammad Rofik Wibowo; Dudi Pratomo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Management of the company can use tax planning strategies in ways that are legal (tax avoidance) or illegal (tax evasion). However, it is crucial to remember that the nation would suffer due to the reduction in one of its primary financial sources. This study examined KAP size, audit duration, audit fees, and tax aggressiveness for companies in the food and beverage subsector listed on the Indonesia Stock Exchange (BEI) between 2017 and 2021. The data was obtained from annual reports that were posted on the official websites of the Indonesian Stock Exchange and other businesses. The sampling strategy employed was purposeful sampling, and 12 businesses were gathered over five years for 60 businesses. The method of analysis used is panel data regression analysis. The results of this study demonstrate the relationship between audit fees, audit duration, KAP size and tax aggressiveness. The size of the KAP, however, impacts tax aggressiveness in the food and beverage subsector companies listed on the Indonesia Stock Exchange between 2017 and 2021. In contrast, audit tenure and audit fees have no impact.